Applying tools of digital economics in view of corruption risk minimization and anti-corruption consciousness shaping - N. V. Mamitova; J. R. Akhmatova (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
Corruption, its scale, specificity and dynamics arise from general political, social and economic problems in the country. Today Russia is not passing only through a process of modernization but a drastic restructuring of public, state, economic, social and psychological foundations. Therefore, we can observe a scientific and practical need in studying issues of corruption counteraction. Corruption offences act as destabilizing factors in society and state functioning. They exert adverse affect on state governance and on public relations in general. Corruption holds back the economic growth of the country, reduces people confidence to the authority. The article investigates new technologies, which are being introduced within the frames of digital economics and considered as tools of corruption minimization. Such methods asanalysis and synthesis were used. The authors provide the definition of the smart-contracts and describe their basic advantages in view of fight against corruption. At the same time key problems arising at legal regulation of block-chain status are discussed. Block-chain technology provides an opportunity to take into account all materialized contradictions in different spheres of public and state life, which form the foundation for corruption, which proliferated actually in all countries of the world. The authors put forward their suggestions dealing with methods and ways of resolving the problem.